Морфологічні особливості пилкових зерен видів триби Coronilleae (Adans.) Boiss. - Карпенко, Н.I.; Савицький, В.Д.; Царик, Н.П. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2008)
Триба Coronillеaе палиноморфологически гетероморфна. Подтверждена целесообразность перенесения Coronilla varia, C. cretica и C. parviflora в род Securigera, а C. emeroides и C. Emerus — в род Hippocrepis. У морфологически близких видов С. varia и C. elegans выявлены довольно существенные отличия по форме ор и структуре покрова пыльцы. Представители Scorpiurus и Ornithopus более отдалены от остальных родов и хорошо отличаются поверхностью покрова пыльцевых зерен. The tribe Coronilleae is heteromorphic according to its palynomorphological characteristics. The practicability of transferring Coronilla varia, C. cretica, C. parviflora to the genus Securigera, ànd C. emeroides, C. emerus — to the genus Hippocrepis has been confirmed. The essential differences in the ora shape and structure of the pollen cover were revealed in morphologically similar C. varia and C. elegans. Representatives of Scorpiurus and Ornithopus are more distant from the rest of genera and are strongly distinguished in their pollen cover.